Activating Both Basal Plane and Edge Sites of Layered Cobalt Oxides for Boosted Water Oxidation. (8th July 2021) - Li, Yu; Chen, Gao; Zhu, Yanping; Hu, Zhiwei; Chan, Ting‐Shan; She, Sixuan; Dai, Jie; Zhou, Wei; Shao, Zongping
Abstract: Layered A x CoO2 materials built by stacking layers of CoO2 slabs and inserting alkali ions in between them have shown a promising activity of oxygen evolution reaction (OER) due to their active edge sites. However, the large basal plane areas of the CoO2 slabs show too strong adsorption energy to the reaction intermediates, which is unfavorable for the release of O2 . Here, a simple cation‐exchange strategy based on Fe 3+ and alkali ions is proposed to simultaneously activate both the basal plane and edge sites of A x CoO2 for the OER. X‐ray absorption spectroscopy has revealed that the Fe 3+ ions deposit both on the surface and edge sites of the CoO2 slabs and enter the interlayer. The cation‐exchanged A x CoO2 electrodes show a boosted activity compared to their pristine and conventional Fe‐doped A x CoO2 counterparts. This phenomenon is mainly ascribed to the abundant edge‐sharing Co–Fe motifs at the edge sites and the charge redistribution in the basal plane sites induced by the insertion of Fe 3+ ions. This work provides a novel method to fully exploit layer‐structured materials for efficient energy conversion. Abstract : A cation‐exchange strategy is proposed to simultaneously activate both the basal plane and edge sites of layered cobalt materials for the oxygen evolution reaction (OER). The as‐prepared materials show better OER activity than the pristine and conventional‐doped materials. This work provides a facile and controllable way to boost the OER performance of the layer structured materials.